Analysis of competition in young soccer players between 16 and 18 years old - Torres-Luque, G.; Cachón Zagalaz, J.; Zagalaz-Sánchez, M. L.; Calahorro, F. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
There have been many studies evaluating soccer competition in adults, however, these investigations are limited during formative stages, which usually have a control of heart rate (Stoyer et al., 2004). The aim of the study is to asses physiological and physical demands during a soccer competition between players from 16 to 18 years old, intending to provide a better understanding of competition at these ages. Methods: Competition assessment consisted of playing a soccer match among 22 players, assessing temporary structure of the game (TS), heart rate (HR), blood lactate concentration ([BL]) and rate of perceived exertion (RPE). The TS was analyzed with a digital camera after establishing Total Time of the Game (TT), Real Time of play (RT) and Non play Time (NT). Control of HR was measured using a Polar Team 2, identifying minimum HR (HRMin), Mean HR (FCMed), Maximum HR (HRMax) and the percentage of maximal HR (%HRMax). To determine [BL] was carried out lactate analyzer LactatePro, completing 5 tests throughout during the game. Finally, every 10 min of the game there was registered RPE using the Borg scale. Results: Results were presented for each period. The TT was 45min 15s, RT was 32min 38s and NT was 12min 53s during First Half. During the second, the TT was 45min 18s, RT 31min 29s, NT 13min 47s. The competition involves an average HR Min of 127,25±18,37 lat/min, HRMed 163,07±7,07 lat/min, HRMax 191,50±7,68 lat/min, %HRMax 80,34 ±3,85. The [BL] and RPE during first half were 4,42±1,63 mmol/l and 14,54±1,57 respectively; and 3,44±1,06 mmol/l and 15,07±1,84 during second half respectively. Discussion: It shows an average and maximum intensity similar to Stroyer et al. (2004) and lower % of MaxHR in Castagna et al. (2009). [BL] and RPE data do not appear to players at formative stages. [BL] results are lower compared with adults (Schulpis et al., 2009), however RPE are similar (Clarke et al., 2008). In addition, there is a tendency to increase RPE the second half on the first. It is observed that there is a great utility in using tools, subjective (RPE) and objective (HR and [BL]) to assess requirements for these ages during a soccer competition.